Implementasi Incentive Compatible Constraints Dalam Pembiayaan Mudharabah: (Studi Pada PT. Bank Syariah Indonesia KCP Stabat) - robi, Robi Naldi Sipahutar (Jurnal Ekonomi dan Keuangan Syariah, 2022)
The mudharabah contract run by Islamic banks is a contract that contains a large opportunity for imperfect information to occur, this is what creates a conflict of interest between the two parties between the shahibul maal and the agent (mudharib), which is called the agency problem. To reduce the possibility of these risks occurring, the Bank can minimize it by setting a number of certain limits when distributing mudharabah financing to mudharib. The purpose of this study was to determine the implementation of ICC at PT. Bank Syariah Indonesia KCP Stabat and ICC viewed from the perspective of Islamic economics. This research is a field research with qualitative methods, primary and secondary data obtained from observations, interviews, and documentation. Respondents who were used as samples in this study were employees of PT. Bank Syariah Indonesia KCP Stabat in the Small Medium Enterprise (SME) division, totaling 3 people. The process of data analysis in this study used descriptive analysis. The results of the study with the implementation of ICC PT. Bank Syariah Indonesia KCP Stabat can minimize the risk caused by asymmetric information. This is evident from the 12 customers of the mudharabah linkage program financing in 2021-2022, who only performed asymmetric information for 1 customer. While in the perspective of Islamic economics the application of ICC is allowed. Because Islam recommends being selective and knowing precisely in choosing someone we will partner with in order to avoid mistakes that can cause losses. Both material and non-material losses. So that the Islamic economic principles of balance and benefit can be achieved.